The Effect of Taxation Socialization, Taxpayer Awareness, Tax Sanctions and Tax Service Quality on Motor Vehicle Taxpayer Compliance - Franata, Michael Sandrico; Khairudin, Khairudin (LPPPIPublishing, 2025)
The financial stability of the state is greatly influenced by taxpayer compliance, which is an important element in the taxation system and increasing national income. The purpose of this study is to analyze the impact of tax socialization, taxpayer awareness, tax sanctions, and the quality of tax services on motor vehicle tax compliance. This study focuses on the development of independent variables, namely the quality of tax services, as a research novelty. Data were obtained through a survey of motor vehicle taxpayers in certain areas and analyzed using descriptive statistical methods and multiple linear regression. This study shows that taxpayer compliance is positively and significantly influenced by tax socialization, taxpayer awareness, tax sanctions, and the quality of tax services. Indicators such as speed of service, information transparency, and effective tax education are key factors in increasing compliance. The practical implications of this study for local governments are the importance of designing strategies that can increase tax revenues, one of which is through improving the quality of tax services and more comprehensive tax education. This study not only adds to the academic literature related to taxpayer compliance, but also provides practical contributions to more effective motor vehicle tax management. These findings are expected to be the basis for making tax policies based on data and empirical evidence.